Recent Advances and Future Challenges in Gastroenterology and Hepatology - Abenavoli, Ludovico; Candelli, Marcello (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Gastroenterology and hepatology are fields of research that have improved considerably in recent years in terms of clinical approach, diagnosis, and therapy. However, there is still much to be clarified and explored, and many questions remain unanswered. Therefore, basic research, including translational and clinical discoveries, supported by technological innovations such as artificial intelligence, will enable further steps toward better, more refined treatments for many digestive diseases. The challenge of modern medicine will therefore be to connect these two fields to ensure optimal patient management. Further innovations will help clinicians to improve clinical practice, establish new guidelines, and provide personalized treatment based on patient characteristics. The aim of this Special Issue is to highlight recent advances and future challenges in gastroenterology and hepatology.